Black blood myocardial T2 mapping. Issue 1 (29th July 2018) - Wang, Chengyan; Jang, Jihye; Neisius, Ulf; Nezafat, Maryam; Fahmy, Ahmed; Kang, Jinkyu; Rodriguez, Jennifer; Goddu, Beth; Pierce, Patrick; Berg, Sophie; Zhang, Jue; Wang, Xiaoying; et al.
Abstract : Purpose: To develop a black blood heart‐rate adaptive T2 ‐prepared balanced steady‐state free‐precession (BEATS) sequence for myocardial T2 mapping. Methods: In BEATS, blood suppression is achieved by using a combination of preexcitation and double inversion recovery pulses. The timing and flip angles of the preexcitation pulse are auto‐calculated in each patient based on heart rate. Numerical simulations, phantom studies, and in vivo studies were conducted to evaluate the performance of BEATS. BEATS T2 maps were acquired in 36 patients referred for clinical cardiac MRI and in 1 swine with recent myocardial infarction. Two readers assessed all images acquired in patients to identify the presence of artifacts associated with slow blood flow. Results: Phantom experiments showed that the BEATS sequence provided accurate T2 values over a wide range of simulated heart rates. Black blood myocardial T2 maps were successfully obtained in all subjects. No significant difference was found between the average T2 measurements obtained from the BEATS and conventional bright‐blood T2 ; however, there was a decrease in precision using the BEATS sequence. A suppression of the blood pool resulted in sharper definition of the blood–myocardium border and reduced partial voluming effect. The subjective assessment showed that 16% (18 out of 108) of short‐axis slices have residual blood artifacts (12 in the apical slice, 4 in the midventricular slice, and 2 in the basal slice). Conclusion: The BEATS sequence yields dark blood myocardial T2 maps with better definition of the blood–myocardium border. Further studies are warranted to evaluate diagnostic accuracy of black blood T2 mapping.